ChemInform Abstract: Broad Scope Aminocyclization of Enynes with Cationic JohnPhos—Gold(I) Complex as the Catalyst. Issue 29 (June 2016) - Miller, Ricarda; Carreras, Javier; Muratore, Michael E.; Gaydou, Morgane; Camponovo, Francesco; Echavarren, Antonio M.
Abstract: The novel aminocyclization of 1, 6‐enynes works well with a wide variety of primary or secondary amines using a robust cationic gold(I) complex.